ETOS KERJA KARYAWAN DALAM MENINGKATKAN PRODUKTIVITAS DI PT HDMS PROFESSIONAL BLITAR PERSPEKTIF EKONOMI ISLAM - Krisdianti, Rita; Santi, Mei (IMTIYAZ: Jurnal Ilmu Keislaman, 2024)
Islam, among the world's religions, is the only religion that upholds the value of work. A job reflects the actual duties, obligations and responsibilities of each individual employee towards their position. In a company, employee work ethic plays an important role in contributing to the progress and decline of a company. In Islam, the work ethic must be based on three elements, namely, monotheism, piety and worship. This means that monotheism (faith in Allah Almighty) causes a person to assess that his work and the results of his work are a means of uniting Allah SWT. However, in the reality of life, there are still many employees, especially Muslims, who are still lazy, undisciplined, unwilling to work hard, and work as they please or what could be called a lack of work ethic. In this research, researchers will examine various types of work ethic that influence company productivity, and how to improve employee work ethic based on an Islamic economic perspective. This research employs a qualitative methodology characterized by a case study approach, emphasizing descriptive analysis.The work ethic of employees at PT HDMS Professional Blitar is fluctuating, meaning that the conditions of each employee are different from one employee to another. Lack of employee work ethic can be overcome by making conditions as comfortable as possible in the workplace and establishing good relationships between employees and company leaders. Keywords: Ethos, Work, Productivity, Economy, Islam.